Quantitative effect of scaffold abundance on signal propagation - Stephen A Chapman; Anand R Asthagiri (Molecular Systems Biology)
Abstract Protein scaffolds bring together multiple components of a signalling pathway, thereby promoting signal propagation along a common physical ‘backbone’. Scaffolds play a prominent role in natural signalling pathways and provide a promising platform for synthetic circuits. To better understand how scaffolding quantitatively affects signal transmission, we conducted an in vivo sensitivity analysis of the yeast mating pathway to a broad range of perturbations in the abundance of the scaffold Ste5. Our measurements show that signal throughput exhibits a biphasic dependence on scaffold concentration and that altering the amount of scaffold binding partners reshapes this biphasic dependence. Unexpectedly, the wild‐type level of Ste5 is ∼10‐fold below the optimum needed to maximize signal throughput. This sub‐optimal configuration may be a tradeoff as increasing Ste5 expression promotes baseline activation of the mating pathway. Furthermore, operating at a sub‐optimal level of Ste5 may provide regulatory flexibility as tuning Ste5 expression up or down directly modulates the downstream phenotypic response. Our quantitative analysis reveals performance tradeoffs in scaffold‐based modules and defines engineering challenges for implementing molecular scaffolds in synthetic pathways.